2006
DOI: 10.1111/j.1365-2036.2006.03086.x
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis: terlipressin therapy for the hepatorenal syndrome

Abstract: SUMMARY BackgroundThe hepatorenal syndrome is a severe and well-known complication of end-stage liver disease, but its management is controversial. Recent reports have shown the efficacy of terlipressin therapy, a vasopressin analogue, in hepatorenal syndrome patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
2
6

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(61 citation statements)
references
References 31 publications
3
50
2
6
Order By: Relevance
“…These results are similar to the HRS reversal data obtained in a recent meta-analysis. 20 The results were also impacted by an imbalance in the number of patients with a baseline SCr level of >7.0 mg/dL (6 in the terlipressin arm vs zero in the control group). None of these patients responded to study treatment or survived (mean survival of 3 days), suggesting that after a certain point the renal failure is not reversible and that patients should be treated early in the course of HRS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are similar to the HRS reversal data obtained in a recent meta-analysis. 20 The results were also impacted by an imbalance in the number of patients with a baseline SCr level of >7.0 mg/dL (6 in the terlipressin arm vs zero in the control group). None of these patients responded to study treatment or survived (mean survival of 3 days), suggesting that after a certain point the renal failure is not reversible and that patients should be treated early in the course of HRS.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 In a meta-analysis of the latter and other uncontrolled trials, terlipressin was reported to reverse HRS type 1 in up to 50% of subjects. 20 We report the results of an international, randomized, double-blind, placebo-controlled, multicenter phase III trial of terlipressin for the treatment of HRS type 1. The specific aim was to define the efficacy and safety of terlipressin vs placebo in addition to supportive medical care including intravenous albumin administration in type 1 HRS.…”
mentioning
confidence: 99%
“…Interestingly, in our cases, ischemic findings were seen only on the scrotal region, without any other ischemic complications involving other parts of the body. As potential predisposing factors facilitating the occurrence of ischemic side effects, a history of ischemic disease, obesity, venous insufficiency, and spontaneous bacterial peritonitis have been reported (4,15,17). When our cases are evaluated accordingly, the first case was obese; however, no predisposing factor facilitating the development of ischemic lesions could be identified in the second case.…”
Section: Discussionmentioning
confidence: 82%
“…Terlipressin gibi vazopressin analoglarının hepatorenal sendromu olan hastaların %40-50'sinde efektif olduğu ve ilk tedavi olarak düşünülmesi gerektiği belirtilmektedir (11)(12)(13)(14). Terlipressin özellikle splanknik yatakta potent vazokonstriktör etki ile efektif kan volümünü artırarak renal perfüzyonu iyileştirir.…”
Section: Hepatorenal Sendromun Yönetimiunclassified